Behavioural thermoregulation via microhabitat selection of winter sleeping areas in an endangered primate: implications for habitat conservation - Liz A. D. Campbell; Patrick J. Tkaczynski; Mohamed Mouna; Abderrahim Derrou; Lahcen Oukannou; Bonaventura Majolo; Els van Lavieren (Royal Society Open Science, 2018)
Strategic microhabitat selection allows animals in seasonally cold environments to reduce homeostatic energy costs, particularly overnight when thermoregulatory demands are greatest. Suitable sleeping areas may therefore represent important resources for winter survival. Knowledge of microhabitat use and potential impacts of anthropogenic habitat modification can aid species conservation through development of targeted habitat management plans. Wild, endangered Barbary macaques (Macaca sylvanus) in logged cedar-oak forest were studied to investigate (1) the hypothesis that macaques select winter sleeping areas with microhabitat characteristics that may reduce thermoregulatory costs, and, if so, (2) how to minimize damage to sleeping areas from logging. Macaques slept only in Atlas cedars (Cedrus atlantica). Consistent with predictions, macaques preferred sleeping in sheltered topography and dense vegetation, which may reduce exposure to wind, precipitation and cold, and preferred large trees that facilitate social huddling. This suggests that Barbary macaques employ strategic nocturnal microhabitat selection to reduce thermoregulatory costs and thus suitable sleeping areas may influence winter survival. To minimize negative impacts of logging on macaque sleeping areas, results suggest avoiding logging in topographical depressions and maintaining cedar densities greater than 250 ha−1 with average breast height greater than 60 cm. This study demonstrates how animal behaviour can be used to guide species-specific habitat management plans.